Studi Akumulasi Rembesan Air Lindi Dengan Menggunakan Metode Geolistrik Resistivitas Konfigurasi Wenner Mapping - Arif Rahman Hakim; Hairunisa Hairunisa; Nurjumiyati Nurjumiyati (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
It has been conducted a research about study of the accumulation of leachate seepage in Supit Urang TPA. The purpose this research to find the location of the accumulation leachate seepage, distribution pattern of the leachate and extent to which leachate can seep. Geological conditions of the area dominated by sandytuf so the ability to absorb leachate is higher than a clay. Resistivity values of the leachate is smaller than resistivity value of water, it is <10 Ohm meter. Study accumulation of leachate seepage laterally was conducted using the Wenner configuration method of geoelectric resistivity mapping. The data acquisition was done using mapping the four line with a length of approximately 150 meters with interval between each point of the line is 10 meters. The results showed, the landfill leachate can seep in almost all directions are north, east and south. However, this leachate seeps more and tend to the east toward resident housing around the landfill. Leachate seepage was also detected to a depth of 24.9 meters and is estimated to reach a radius of 500 meters from the landfill, the seepage reaches resident housing around the landfill.